PERAN FISIOLOGIS SARI KEDELAI HITAM DIPERKAYA MIKROENKAPSULAN MINYAK SAWIT MENTAH PADA PENDERITA DIABETES MELITUS TIPE-2 - Reno Irwanto; Dede Robiatul Adawiyah; Fransiska Rungkat Zakaria (Jurnal Teknologi dan Industri Pangan, 2016)
Diabetes mellitus type-2 (DM-2) is a disease characterized by high level of blood glucose which may result in complications of other diseases. Currently, the  disease prevalence of DM-2 has been  increasing. Appropriate diet patterns can be a solution for DM-2 control. Black soybean milk (BSM) enriched with microencapsulated crude palm oil (CPO) is an example. The objective of the study was to determine the effectiveness of BSM containing microencapsulated CPO in controlling and improving the condition of DM-2 patients. The intervention consist 2 group with 15 people DM-2 was given BSM 240 mL containing 0.4 g microencapsulated CPO daily for 28 days, while a control group with 11 people DM-2 without intervention product. Data were analyzed using software SPSS 15.0 with student-t test at significant level α=5%. Medicines prescribed to all volunteer were not terminated during the intervention period. The microencapsulated CPO usedin this study has a moisture content of 1.77±0.15%, solubility value of 65.39±2.71%, and total carotene of 295.24±7.40 ppm while BSM has protein content of 2.76±0.13%, fat 1.17±0.06%, ash 0.12±0.08%, moisture 94.69±0.04%, and carbohydrate (by difference) 1.27±0.10%. The consumption of BSM containing microencapsulated CPO showed insignificant effects on Fasting Blood Glucose (FBG) levels (P>0.05), but significantly reduced cyclooxygenase 2 levels (P<0.05) and MDA levels (P<0.05). The control group showed insignificant differences for FBG (P>0.05), cyclooxygenase 2 (P<0.05), and MDA level (P>0.05). The significant changes indicated that BSM containing microenca-psulated CPO has against DM-2 disease.